2011
DOI: 10.1038/gene.2010.77
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dysregulates and silences the HLA-DQ locus by altering chromatin architecture

Abstract: The MHC-II locus encodes a cluster of highly polymorphic genes HLA-DR, -DQ, and -DP that are co-expressed in mature B lymphocytes. Two cell lines were established over 30 years ago from a patient diagnosed with acute lymphocytic leukemia. Laz221 represented the leukemic cells of the patient; whereas Laz388 represented the normal B cells of the patient. Whereas Laz388 expressed both HLA-DR and HLA-DQ surface and gene products, Laz221 expressed only HLA-DR genes. The discordant expression of HLA-DR and HLA-DQ ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…DNA methylation is known to reduce CTCF binding (10). Therefore, 5-azacytidine-induced inhibition of B-cell alloantigen presentation, and increased HLA-DOA expression in our experiments, may have also resulted from enhanced affinity of CTCF to its binding site (26).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is known to reduce CTCF binding (10). Therefore, 5-azacytidine-induced inhibition of B-cell alloantigen presentation, and increased HLA-DOA expression in our experiments, may have also resulted from enhanced affinity of CTCF to its binding site (26).…”
Section: Discussionmentioning
confidence: 99%
“…The haplotype comprises rs9271597, rs9271600, and rs9271601, which are in perfect linkage disequilibrium and span just 47 nucleotides within an ENCODE (9) transcriptional element (chr6:32588500-32597000), which has the characteristics of a super-enhancer (13,14). This region has been also suggested to harbor a transcriptional insulator (18), and thus the high-risk haplotype might mediate a complex pattern of transcriptional activation or de-repression in permissive cells. Together with correspondence of these SNPs to an expression quantitative trait locus for HLA-DR and HLA-DQ RNA expression (15), these findings suggested that increased vitiligo risk might result from higher surface levels of HLA-DR or HLA-DQ, possibly resulting in enhanced presentation of self-antigens and associated with increased production of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the intergenic region between HLA-DQA1 and HLA-DRB1, is characterized by the presence of a CTCF-binding CCCTC sequence, XL9, of high histone acetylation and of particular importance for the control of the expression of both HLA genes and for the chromatin architecture of the MHC class II locus. [18][19][20][21] The fact that CTCF expression is increased and transcription of HLA DQA1 and HLA DRB1 is decreased in the IQ À group could be in favor to a repressor role for CTCF. On the other hand, the RFX1 gene, coding for a protein that binds to the X-boxes of MHC class II genes and which is essential in their expression, shows a three-fold decreased level of expression in the IQÀ group in comparison to the IQ þ group.…”
Section: Gene Expression and Iq In Trisomy 21mentioning
confidence: 99%